2019
DOI: 10.1002/jsfa.10111
|View full text |Cite
|
Sign up to set email alerts
|

Expression profiles of glucosinolate biosynthetic genes in turnip (Brassica rapa var. rapa) at different developmental stages and effect of transformed flavin‐containing monooxygenase genes on hairy root glucosinolate content

Abstract: BACKGROUND: Glucosinolates (GSLs) are secondary metabolites, mainly existing in Brassica vegetables. Their breakdown products have health benefits and contribute to the distinctive taste of these vegetables. Because of their high value, there is a lot of interest in developing breeding strategies to increase the content of beneficial GSLs in Brassica species. GSLs are synthesized from certain amino acids and their biological roles depend largely on the structure of their side chains. Flavin-containing monooxyg… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
5
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 14 publications
(6 citation statements)
references
References 44 publications
1
5
0
Order By: Relevance
“…Specifically, MAM controls the variability in aliphatic GSL carbon chain length, whereas AOP is responsible for modification of side chain structure ( Benderoth et al., 2009 ; Liu et al., 2014 ). Detailed analysis of five Brassica species in this study revealed considerable variation in the relative content of aliphatic GSLs among species and subspecies, consistent with the findings of earlier studies ( Chen et al., 2008 ; Yang et al., 2020 ). Previous research confirmed that there were significant differences in the GSL content of Chinese cabbage (Chiifu) germplasm, due largely to genetic changes because of selection pressure influenced by consumer preference ( Kang et al., 2006 ).…”
Section: Discussionsupporting
confidence: 91%
See 2 more Smart Citations
“…Specifically, MAM controls the variability in aliphatic GSL carbon chain length, whereas AOP is responsible for modification of side chain structure ( Benderoth et al., 2009 ; Liu et al., 2014 ). Detailed analysis of five Brassica species in this study revealed considerable variation in the relative content of aliphatic GSLs among species and subspecies, consistent with the findings of earlier studies ( Chen et al., 2008 ; Yang et al., 2020 ). Previous research confirmed that there were significant differences in the GSL content of Chinese cabbage (Chiifu) germplasm, due largely to genetic changes because of selection pressure influenced by consumer preference ( Kang et al., 2006 ).…”
Section: Discussionsupporting
confidence: 91%
“…GSLs and the products of their hydrolysis are determinants of the unique taste of Brassica crops ( Bell et al., 2018 ). Compared with other Brassica species, turnips contain more aliphatic GSLs ( Yang et al., 2020 ). On the basis of the pseudogene functional annotations, we analyzed the genes involved in the aliphatic GSL metabolic pathway ( Figure 4 A and Supplemental Figure 12 ); these genes are the predominant GSL-related genes in the Brassica AA genome.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Vegetable crops harbor a greater number of homologous genes associated with GS biosynthesis than those identified in Arabidopsis [ 36 ]. However, in Chinese kale, the homologs that play a crucial role in a specific metabolic process remain unknown, rendering it impossible to utilize gene editing for the improvement of vegetable quality.…”
Section: Introductionmentioning
confidence: 99%
“…Increased amount of aliphatic GSLs was also observed in turnip (Brassica rapa var. rapa) hairy roots when overexpressing FMO GS-OX genes (Yang et al 2019).…”
Section: Engineering Enzyme Genesmentioning
confidence: 99%